2019
DOI: 10.3390/antiox8080246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Antioxidant Properties of Extra Virgin Olive Oil after Cooking Typical Mediterranean Vegetables

Abstract: Extra virgin olive oil (EVOO), water, and a water/oil mixture (W/O) were used for frying, boiling and sautéeing Mediterranean vegetables (potato, pumpkin, tomato and eggplant). Differences in antioxidant capacity (AC) (2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric iron (FRAP), 2,2-azinobis-(3-ethylbensothiazoline)-6-sulphonic acid (ABTS)), total phenolic content (TPC) and individual phenols (high-performance liquid chromatography (HPLC)) in unused and used EVOO and water were determined. The water used to boil … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 69 publications
3
35
0
Order By: Relevance
“…However, at a high temperature, its degradation is more likely to occur, resulting in a substantial reduction. Similar results are observed by Ramírez-Anaya et al (2019), who showed that after sautéing typical Mediterranean vegetables at 100 • C, the hydroxytyrosol content only decreased between 25% and 50% [33]. Furthermore, a similar behavior was found by Krichene et al (2015), who showed an increase in hytroxytyrosol concentration during the first months of storage due to the transformation of oleuropein and derivates in the compound, but after some months there was a high decrease in its concentration [42].…”
Section: Phenolic Alcohols and Otherssupporting
confidence: 85%
See 1 more Smart Citation
“…However, at a high temperature, its degradation is more likely to occur, resulting in a substantial reduction. Similar results are observed by Ramírez-Anaya et al (2019), who showed that after sautéing typical Mediterranean vegetables at 100 • C, the hydroxytyrosol content only decreased between 25% and 50% [33]. Furthermore, a similar behavior was found by Krichene et al (2015), who showed an increase in hytroxytyrosol concentration during the first months of storage due to the transformation of oleuropein and derivates in the compound, but after some months there was a high decrease in its concentration [42].…”
Section: Phenolic Alcohols and Otherssupporting
confidence: 85%
“…For this reason, it is also difficult to compare the results with those showed by one recent study, in which the degradation of the total phenolic content during a sautéing process was evaluated. The authors showed a decrease of approximately 50% of the antioxidant capacity measured by the Folin-Ciocalteau method after sautéing typical Mediterranean vegetables (potato, eggplant, tomato, and pumkin) for 10 min at 100 • C [33]. For the ANOVA and multiple regression models, the normality of residuals was verified.…”
Section: Total Polyphenolsmentioning
confidence: 89%
“…At high temperatures, saturates and monounsaturates undergo negative alterations to a much lesser extent than sensitive polyunsaturated acids, which account for no more than 10–12% of olive oil. Olive oil abounds in polyphenols and vitamin E. They reduce the pace of harmful changes induced by high temperatures [ 26 , 27 , 28 ]. Molina-Garcia et al [ 29 ] compared three types of fat: extra virgin olive oil, walnut oil, and rapeseed oil.…”
Section: Resultsmentioning
confidence: 99%
“…The method derived the ferric reducing ability of FRAP according to the procedure described by Benzie and Strain [ 35 ] and the antioxidant equivalent capacity as radical scavenging activity, based on reduction of the radical cation ABTS assay following the procedure of Re et al [ 36 ]. These assays were modified in our laboratory and these methods have been described in depth by our research group [ 37 , 38 , 39 , 40 , 41 ]. In all of the methods applied, we determined the dilution of persimmon methanolic extracts that gave a linear response.…”
Section: Methodsmentioning
confidence: 99%